2021
DOI: 10.1021/acs.orglett.1c02435
|View full text |Cite
|
Sign up to set email alerts
|

Collective Asymmetric Total Syntheses of Marine Decahydroquinoline Alkaloid Lepadins A–E, H, and ent-I

Abstract: Lepadins are cis-fused decahydroquinoline (DHQ) marine alkaloids that have shown diverse biological activities and have attracted extensive synthetic interest. A new collective synthetic strategy is reported that features a green chemistry approach for constructing the common cis-fused DHQ core, which is achieved through green oxone-halide oxidation for both the aza-Achmatowicz rearrangement and the intramolecular [3 + 2] cycloaddition of nitrile oxide–alkene. Collective total syntheses of lepadins A–E and H a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…These AchR-based strategies are usually more efficient and more flexible than the related previous syntheses, as exemplified by our syntheses of (i) a series of 6,8-dioxabicyclo-[3.2.1]octane (6,8-DOBCO) complex natural products (Figure 1C) 1,54 and (ii) decahydroquinoline alkaloid lepadins (Figure 1F). 55 Additionally, the AchR-based strategy allowed us to address the synthetic challenge of diastereoselective construction of trans-2,6tetrahydropyran present in many natural products 52a,56 (i.e., musellarins, Figure 1B). By using the AchR-based strategy, we have accomplished the total syntheses of >28 natural products, including the structurally complex uprolides 57 and paspalines 1 (Figure 1).…”
Section: Application Of Achmatowicz Rearrangement In Total Synthesis ...mentioning
confidence: 99%
See 1 more Smart Citation
“…These AchR-based strategies are usually more efficient and more flexible than the related previous syntheses, as exemplified by our syntheses of (i) a series of 6,8-dioxabicyclo-[3.2.1]octane (6,8-DOBCO) complex natural products (Figure 1C) 1,54 and (ii) decahydroquinoline alkaloid lepadins (Figure 1F). 55 Additionally, the AchR-based strategy allowed us to address the synthetic challenge of diastereoselective construction of trans-2,6tetrahydropyran present in many natural products 52a,56 (i.e., musellarins, Figure 1B). By using the AchR-based strategy, we have accomplished the total syntheses of >28 natural products, including the structurally complex uprolides 57 and paspalines 1 (Figure 1).…”
Section: Application Of Achmatowicz Rearrangement In Total Synthesis ...mentioning
confidence: 99%
“…In the last section of this Account, we demonstrate the utility of aza-AchR in the total synthesis of lepadins A−K (Scheme 16). 55 Lepadins are a family of decahydroquinoline (DHQ) alkaloids isolated from marine invertebrate animals and they exhibit significant biological activities. We proposed a new synthetic strategy that exploited aza-AchR and intramolecular nitrile oxide cyclization to construct the DHQ core (Scheme 16).…”
Section: Collective Total Syntheses Of Lepadins A−e H and Ent-i (Pipe...mentioning
confidence: 99%
“…However, the synthesis of lepadins requires a conspicuous number of highly stereoselective synthetic steps which represents a not easily accessible route for obtaining the native metabolites. Indeed, only recently, Tong et al have reported a more attractive synthetic strategy for constructing the common cis-fused decahydroquinoline ring of several lepadins by a green chemistry approach [17]. For this reason, the isolation of new examples of lepadin alkaloids remains a key factor to enlarge the great chemodiversity associated to this chemical class, and to provide further new structural motifs that can represent a valuable resource both to grow up the knowledge on their bioactivities and to assess accordingly structure-activity relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Lepadins are cis -fused decahydroquinoline (DHQ) marine alkaloids that have shown diverse biological activities and have attracted extensive synthetic interest [ 41 ]. In this study we found that lepadin A shows cytotoxic effect against cancer cells together with maturation of mouse DCs at micromolar concentrations.…”
Section: Discussionmentioning
confidence: 99%